Galenic validation of plasma rich in growth factors eye drops - Eduardo Anitua; Francisco Muruzábal; Ana Riestra; María de la Fuente; Jesús Merayo-Lloves (Farmacia Hospitalaria)
Objective: Galenic evaluation of the process for obtaining and storing the platelet rich in growth factors PRGF-Endoret® eye drops. Method: To assess whether the PRGF-Endoret® eye drops process is aseptically obtained, a sterility test was carried out on the eye drops; the tightness of the PRGF-Endoret® eye drops containers was also analyzed. Likewise, the chemical and biological properties of the PRGF- Endoret® eye drops were evaluated after the obtaining process and storage. Eye drop filtration tests, one cycle of freezing at –20 °C and thawing, and eye drop stability for three and six months stored at –20 °C were included. Results: The results obtained in the sterility test showed no microbial contamination in any of the analyzed eyedropper; tightness test showed that 100% of the eyedrop containers and the 98.4% of the plugs analyzed remained hermetic. On the other hand, all the growth factors measured remained constant after filtering the PRGF-Endoret® eye drops. Furthermore, the different eye drop stability tests carried out in this study showed no significant changes in the growth factors levels, cell proliferative activity or in the chemical characteristics analyzed. Conclusions: The PRGF-Endoret® eye drops are obtained in a safety and aseptic manner following the guidelines issued by the Spanish Agency for Drugs and Health Products and the Ministry of Health to obtain medicines for human use. The PRGF-Endoret® eye drops maintain their physical-chemical and biological properties after being subjected to different storage times and temperatures.